2015
DOI: 10.1136/bmjstel-2015-000040
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of opportunities for early-stage paramedicine students to practice clinical skills during clinical placements compared with an equal dose of simulation-based workshops

Abstract: . Quantification of opportunities for early-stage paramedicine students to practice clinical skills during clinical placements compared to an equal dose of simulation-based workshops,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Across healthcare, a theory/practice education gap is well identified in the literature including nursing (48), allied health (49) and paramedicine (23). Our participants suggested that although graduates are typically technically competent, they still lacked organisational and health systems knowledge, critical judgement and clinical decision-making skills.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Across healthcare, a theory/practice education gap is well identified in the literature including nursing (48), allied health (49) and paramedicine (23). Our participants suggested that although graduates are typically technically competent, they still lacked organisational and health systems knowledge, critical judgement and clinical decision-making skills.…”
Section: Discussionmentioning
confidence: 90%
“…the disparity across availability and enthusiasm of mentors, an uncontrollable case-mix presentation, and students rarely assuming overall responsibility for patients). Some barriers to participation on clinical practicum have been identified in previous research (23), and more research is required on how specific barriers to clinical practicums can be overcome as a means to graduating more prepared paramedics and thus reducing the time period for supervised practice. There are a suite of professional competencies defined in both jurisdictions (13,15) and accredited universities are graduating students who meet those competencies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Embedding realistic night shift training through simulation not only replicates real life practice, but also has the ability to provide a high level of consistent clinical practice exposure across the course of an undergraduate degree, something that has previously been identified as an uncontrollable deficit of the traditional clinical placement model (25,26). This research advocates for the inclusion of simulated night shifts into the standard undergraduate curricula as it is perceived by students to be realistic, enjoyable and to provide a valuable learning experience.…”
Section: Discussionmentioning
confidence: 96%
“…This simulation exercise allowed participants to not only experience the lifecycle of each job (scenario) from dispatch to handover at hospital, but also repeating this over the course of a 13-hour long shift as would happen in real-world practice. Furthermore, the simulated nature of the scenarios allowed for consistency across scenarios ensuring all participants received the same learning experience, which is not possible from learning occurring within the clinical placement setting that is reliant on random patient presentation (25)(26). Furthermore, the learning experience was able to be provided to undergraduate paramedic students with pre-existing equipment and infrastructure, utilisation of voluntary patient actors (in-kind contribution), and with only a small budget of approximately AUD700 for vehicle fuel.…”
Section: Strengths and Limitationsmentioning
confidence: 99%